An endometrial histomorphometric study of CD56+ natural killer cells in women with unexplained infertility - M Muller; G Kalmeier; P Eyal; A de Bruin; R Pool; C du Rant; R Ehlers; A Stander; A van Schoor; E Nortje; P du Toit (South African Medical Association, 2017)
Background. The number of peripheral blood and endometrial natural killer cells varies greatly during implantation and the first trimester of pregnancy and is thought to play a role in the maintenance of a healthy pregnancy. However, the role of endometrial CD56+ natural killer (NK) cells as an immunological mechanism in unexplained infertility is yet unknown.Objectives. The study aimed to enumerate the concentrations of CD56+ NK cells in endometrial samples, and to statistically compare these numbers between fertile and infertile women.Methods. A histomorphometric analysis was conducted using haematoxylin and eosin staining and an immunohistochemical approach was used for quantifying cell numbers.Results. Fifty samples were collected in equal parts between a study group of infertile female subjects (mean (standard deviation) age 35 (4), range 26 - 42 years) and a control group of multiparous fertile individuals (mean (SD) age 43.4 (6.3), range 30 - 55). The mean number of CD56+ NK cells present at different depths for both the study and control groups did not differ significantly. Age and group (study or control) were not significantly related to the mean number of CD56+ NK cells. However, for the late secretory phase the mean number of CD56+ NK cells was significantly higherthan for the early phase.Conclusion. Our findings could not identify a statistically significant correlation between the number of CD56+ NK cells and infertility.